2013
DOI: 10.1007/s00436-013-3563-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: The acaricidal efficacy of peracetic acid and deltamethrin against the fowl tick, Argas persicus, infesting laying hens

Abstract: The fowl tick, Argas persicus (Oken), is of veterinary importance as a parasite of poultry and wild birds. The antitick efficacy, in vitro and in vivo, of peracetic acid (PAA) and deltamethrin (DMT) was tested separately against A. persicus through the dipping technique. PAA (0.5%) was highly efficient against soft tick larvae (A. persicus), resulting in 100 % mortality after 2 min. The lethal concentrations LC₅₀ and LC₉₅ were 0.310 and 0.503 %, respectively. The lethal time values LT₅₀ and LT₉₅ were 5.34 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The fowl tick has been previously described morphologically in the Mediterranean basin and in Algeria [8] . As demonstrated by recent reported cases, the potential role of this tick as a pathogen vector, especially in the case of severe infestations, makes this species of great public health concern and an invasive species to control [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The fowl tick has been previously described morphologically in the Mediterranean basin and in Algeria [8] . As demonstrated by recent reported cases, the potential role of this tick as a pathogen vector, especially in the case of severe infestations, makes this species of great public health concern and an invasive species to control [17] .…”
Section: Discussionmentioning
confidence: 99%
“…A related study showed that the methanol extract of neem and Citrullus colocynthis produced an acaricidal effect against adult females, eggs, and larvae, and neem was more effective against H. dromedarii [72]. Some other materials are also effective in vitro acaricides such as peracetic acid against Boophilus annulatus and the fowl tick, Argas persicus [17] and A. persicus, infesting laying hens [18]. Moreover, some photosensitizers such as safranin and rose bengal had a strong acaricidal effect against H. dromedarii and suppressed the reproductive potential of its engorged females [16].…”
Section: Effect Of the Plant Resin Extracts On Arthropodsmentioning
confidence: 99%
“…Some other approaches could be used for controlling pests, such as botanicals and biological control, vaccination, photopesticides, and acids [16][17][18][19][20][21][22][23]. Searching for alternative control strategies, mainly from plant-based resources, is a promising field [5].…”
Section: Introductionmentioning
confidence: 99%
“…AcrossgloballyArgas persicus was globally distributed including tropical and sub-tropical areas of the world [40]., that is known as a fowl parasite with veterinary importance. "It serves as the vector of avian spirochaetosis (Borrelia anserina) and aegyptianellosis (Aegyptianella pullorum)", [41,42].…”
Section: Discussionmentioning
confidence: 99%